102 The cost of misdiagnosis in POEMS syndrome. Issue 6 (27th May 2022) - Keddie, Stephen; Marsh, Eleanor; D'Sa, Shirley; Terris-Prestholt, Fern; Lunn, Michael
Abstract : Background: POEMS syndrome is a rare cause of neuropathy misdiagnosed as Chronic Inflammatory Demyelinating Polyradiculoneuropathy (CIDP) in 60% of cases. Ineffective CIDP directed therapy is expensive, introduces risk of complications, and often results in disease progression. Vascular endothelial growth factor (VEGF) is a sensitive and specific biomarker in the diagnosis of POEMS syndrome costing approximately £50. Introducing early directed screening with VEGF more accurately distinguishes POEMS syndrome from CIDP than the current standard of care (SOC). Methods: 100 cases from the UCLH POEMS database were selected. We grouped patients according to diagnostic pathway and compared health outcomes. We conducted a model-based cost-effectiveness analysis to compare diagnostic outcomes and costs of the current SOC with intervention pathways using VEGF screening. We used a study cohort of 1, 250 patients with polyneuropathy (UK incidence) and conducted costing from a health-services perspective. Results: Treatments associated with POEMS misdiagnosis led to a total healthcare expenditure in our cohort of £808, 550-£1, 111, 756 over 20 years, with an average cost-per-POEMS-syndrome-patient misdiagnosed of £14, 701-£20, 214. Our intervention pathway which introduces VEGF screening into the current SOC results in 4 additional early POEMS diagnoses per year and a cost-saving of almost £40, 000 through avoidance of non-POEMS directed therapy and related hospital costs. Conclusion: VEGF testing should be routine for patients presenting with an acquired demyelinating neu- ropathy. This will improve early diagnosis of POEMS syndrome, enable effective therapy and reduce cos8ts5. stephen.keddie@nhs.net